An ultrasensitive electrochemiluminescence biosensor for the detection of total bacterial count in environmental and biological samples based on a novel sulfur quantum dot luminophore. Issue 8 (25th March 2022) - Wang, Xiaobin; Zhao, Yuqing; Hua, Qing; Lu, Jiaojiao; Tang, Feiyan; Sun, Wenjie; Luan, Feng; Zhuang, Xuming; Tian, Chunyuan
Abstract : An electrochemiluminescence sensor for total bacterial count detection based on sulfur quantum dots with β-nicotinamide adenine dinucleotide as an important parameter. Abstract : In this paper, the electrochemiluminescence (ECL) of sulfur quantum dots (SQDs) in a potassium persulfate cathodic co-reactant was studied. Based on the selective quenching of the ECL emission from the SQDs by β-nicotinamide adenine dinucleotide (NADH), an ultrasensitive ECL biosensor with NADH as an important parameter was established for the highly sensitive and selective detection of total bacterial count (TBC). A linear response between the ECL intensity and the NADH concentration in the range of 1 pM to 10 μM was obtained, thus achieving a detection limit of 1 pM. As the content of NADH in cells is positively correlated with the TBC, a sensor has been successfully applied to detect the TBC in actual water samples with a good recovery rate of 10 3 –10 7 CFU mL −1 . This study provides a green and feasible method for TBC detection in the environment.